Direct Endoscopic Necrosectomy With and Without Hydrogen Peroxide for Walled-off Pancreatic Necrosis: A Multicenter Comparative Study. (3rd April 2021) - Messallam, Ahmed A.; Adler, Douglas G.; Shah, Raj J.; Nieto, Jose M.; Moran, Robert; Elmunzer, B. Joseph; Cosgrove, Natalie; Mullady, Dan; Singh, Harkirat; Cote, Gregory; Papachristou, Georgios I.; Othman, Mohamed O.; et al.
Abstract : INTRODUCTION: Endoscopic necrosectomy has emerged as the preferred treatment modality for walled-off pancreatic necrosis. This study was designed to evaluate the safety and efficacy of direct endoscopic necrosectomy with and without hydrogen peroxide (H2 O2 ) lavage. METHODS: Retrospective chart reviews were performed for all patients undergoing endoscopic transmural management of walled-off pancreatic necrosis at 9 major medical centers from November 2011 to August 2018. Clinical success was defined as the resolution of the collection by imaging within 6 months, without requiring non‐endoscopic procedures or surgery. RESULTS: Of 293 patients, 204 met the inclusion criteria. Technical and clinical success rates were 100% (204/204) and 81% (166/189), respectively. For patients, 122 (59.8%) patients had at least one H2 O2 necrosectomy (H2 O2 group) and 82 (40.2%) patients had standard endoscopic necrosectomy. Clinical success was higher in the H2 O2 group: 106/113 (93.8%) vs 60/76 (78.9%), P = 0.002. On a multivariate analysis, the use of H2 O2 was associated with higher clinical success rate (odds ratio 3.30, P = 0.033) and earlier resolution (odds ratio 2.27, P < 0.001). During a mean follow-up of 274 days, 27 complications occurred. Comparing procedures performed with and without H2 O2 (n = 250 vs 183), there was no difference in post‐procedure bleeding (7 vs 9, P = 0.25), perforation (2 vs 3, P = 0.66), infection (1 vs 2, P = 0.58), or overall complication rate (n = 13 [5.2%] vs 14 [7.7%], P = 0.30). DISCUSSION: H2 O2 -assisted endoscopic necrosectomy had a higher clinical success rate and a shorter time to resolution with equivalent complication rates relative to standard necrosectomy.See the visual abstract at http://links.lww.com/AJG/B714 .